2022
DOI: 10.1098/rsbl.2022.0155
|View full text |Cite
|
Sign up to set email alerts
|

Dance-communicated distances support nectar foraging as a supply-driven system

Abstract: Much like human consumers, honeybees adjust their behaviours based on resources' supply and demand. For both, interactions occur in fluctuating conditions. Honeybees weigh the cost of flight against the benefit of nectar and pollen, which are nutritionally distinct resources that serve different purposes: bees collect nectar continuously to build large honey stores for overwintering, but they collect pollen intermittently to build modest stores for brood production periods. Therefore, nectar foraging can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…While nectar and honeydew are stored in large quantities in the hive, pollen stores last no longer than a few days and thus need to be supplied depending on the amount of brood that is being reared at different times during the season (Seeley, 1995). Based on data of two dance decoding studies from England (Balfour & Ratnieks, 2017; Couvillon et al, 2015) and data collected in three different landscape types in the United States, Ohlinger et al (2022) reasoned that nectar foragers might provide a better indicator of general forage availability as these three studies found larger distances for nectar than for pollen foraging. Our data from a forest‐dominated landscape (Figure S5) and data from agricultural (Steffan‐Dewenter & Kuhn, 2003) and suburban areas (Waddington et al, 1994) contradict these findings (larger foraging distances during pollen foraging).…”
Section: Discussionmentioning
confidence: 99%
“…While nectar and honeydew are stored in large quantities in the hive, pollen stores last no longer than a few days and thus need to be supplied depending on the amount of brood that is being reared at different times during the season (Seeley, 1995). Based on data of two dance decoding studies from England (Balfour & Ratnieks, 2017; Couvillon et al, 2015) and data collected in three different landscape types in the United States, Ohlinger et al (2022) reasoned that nectar foragers might provide a better indicator of general forage availability as these three studies found larger distances for nectar than for pollen foraging. Our data from a forest‐dominated landscape (Figure S5) and data from agricultural (Steffan‐Dewenter & Kuhn, 2003) and suburban areas (Waddington et al, 1994) contradict these findings (larger foraging distances during pollen foraging).…”
Section: Discussionmentioning
confidence: 99%